An in vitro method to test the safety and efficacy of low-level laser therapy (LLLT) in the healing of a canine skin model. Issue 1 (December 2016) - Gagnon, Dominique; Gibson, Thomas; Singh, Ameet; zur Linden, Alex; Kazienko, Jaimie; LaMarre, Jonathan
Abstract Background Low-level laser therapy (LLLT) has been used clinically as a treatment modality for a variety of medical conditions including wound-healing processes. It is an attractive and emerging method to enhance wound healing and improve clinical outcomes both in human and veterinary medicine. Despite the fact that the use of LLLT continues to gain in popularity, there is no universally accepted theory that defends all its cellular effects and beneficial biological processes in tissue repair. The present study was designed to evaluate the effect of LLLT on cellular migration and proliferation of cultured canine epidermal keratinocytes (CPEK) in an in vitro wound healing model. Results Keratinocyte migration and proliferation were assessed using a scratch migration assay and a proliferation assay, respectively. Fifteen independent replicates were performed for each assay. Canine epidermal keratinocyte cells exposed to LLLT with 0.1, 0.2, and 1.2 J/cm2 migrated significantly more rapidly (p < 0.03) and showed significantly higher rates of proliferation (p < 0.0001) compared to non-irradiated cells cultured in the same medium and cells exposed to the higher energy dose of 10 J/cm2 . Irradiation with 10 J/cm2 was characterized by decreased cellular migration and proliferation. These results revealed that LLLT has a measurable, dose-dependent effect on two different aspects of keratinocyte biology in vitro. Conclusion In this in vitro wound-healing model, LLLT increased cellular migration and proliferation at doses of 0.1, 0.2, and 1.2 J/cm2 while exposure to 10 J/cm2 decreased cellular migration and proliferation. These data suggest that the beneficial effects of LLLT in vivo may be due, in part, to effects on keratinocyte behavior.